286. Exploratory Cost-Effectiveness Analysis for Treatment of Methicillin-Resistant Staphylococcus aureus Bloodstream Infections: Are Daptomycin and Linezolid Favored over Vancomycin and Other Antibiotics?. (31st December 2020) - Vu, Michelle; Smith, Kenneth; Aspinall, Sherrie L; Clancy, Cornelius J; Buehrle, Deanna
Abstract: Background: Methicillin-resistant Staphylococcus aureus bloodstream infections (MRSAB) cause significant mortality and often require extended antibiotic therapy. Vancomycin, the most common initial MRSAB treatment, carries significant monitoring burden and nephrotoxicity risks. We compared cost-effectiveness of vancomycin and other antibiotic regimens as MRSAB treatment. Methods: We estimated cost-effectiveness of intravenous antibiotics (vancomycin, daptomycin, linezolid, ceftaroline/daptomycin, dalbavancin) for Veterans Health Administration (VA) patients with MRSAB using an exploratory decision-tree model. Primary effectiveness outcome was composite of microbiological failure and adverse drug event (ADE)-related discontinuation at 7-days. Results: In base-case analyses, linezolid and daptomycin were less expensive and had fewer treatment failures than other regimens at 4 and 6-weeks. Compared to linezolid, daptomycin incremental cost-effectiveness ratios were ~$45, 000 (4-weeks) and ~$61, 000 (6-weeks) per composite failure avoided, respectively. In one-way sensitivity analyses, daptomycin (4-weeks) was favored over linezolid if linezolid microbiological failure or ADE-related discontinuation rates were >14.8% (base case: 14.0%) or >14.3% (base case: 14.0%), respectively, assuming a willingness to pay (WTP) threshold of $40, 000/ composite treatment failure avoided. Vancomycin was favored if its microbiological failure risk was < 16.4% (base case: 27.2%). In two-way sensitivity analyses, daptomycin was favored if linezolid microbiological failure and ADE-related discontinuation rates were >19% and > 16%, respectively. Linezolid, daptomycin and vancomycin were favored in 47%, 39%, and 11% of 4-week probabilistic iterations, respectively, at $40, 000 WTP. Conclusion: Daptomycin or linezolid are likely less expensive and more effective than vancomycin or other initial regimens for MRSAB. More data are needed to support safety of linezolid in MRSAB patients. Disclosures: Cornelius J. Clancy, MD, Astellas (Consultant, Grant/Research Support)Cidara (Consultant, Research Grant or Support)Melinta (Grant/Research Support)Merck (Consultant, Grant/Research Support)Needham Associates (Consultant)Qpex (Consultant)Scynexis (Consultant)Shionogi (Consultant)